Preparation of a novel flame retardant containing triazine groups and its application on cotton fabrics. (24th April 2020) - Sun, Ling; Wang, Shihao; Zhang, Jiaojiao; Li, Wennan; Lu, Zhou; Zhang, Zheng; Zhu, Ping; Dong, Chaohong
Abstract : A novel triazine-based flame retardant capable of reacting with natural cellulose fiber was successfully synthesized and used to improve the flame retardancy of cotton fabrics. Abstract : In order to improve the flame retardancy of cotton fabrics and reduce their fire risk, a novel triazine-based flame retardant, (3-((6-((4, 6-dichloro-1, 3, 5-triazin-2-yl)amino)hexyl)amino)-3-oxopropyl)(phenyl)phosphinic acid (CPHDT), was successfully synthesized with 3-hydroxyphenylphosphinyl-propanoic acid, 1, 6-diaminohexane and cyanuric chloride. The structures of (3-((6-aminohexyl)amino)-3-oxopropyl)(phenyl)phosphinic acid (intermediate I), CPHDT, and CPHDT-treated cotton fabrics (at different heating temperatures) were analyzed by Fourier transform infrared (FTIR) spectroscopy. The flame retardancy of CPHDT-treated cotton fabrics was studied by limiting oxygen index (LOI) and vertical flammability test. The results showed that the limiting oxygen index value of cotton fabrics treated by 400 g L −1 CPHDT was 28.1%, which was 10.1% higher than that of pure cotton fabrics. The vertical flammability test demonstrated that the after-glow time and after-flame time of CPHDT-treated cotton fabrics were immensely shortened compared with those of pure cotton fabrics. The thermogravimetric (TG) analysis and scanning electron microscopy (SEM) showed that the cotton fabrics treated with CPHDT exhibited good thermal stability and char-forming ability compared to pure cotton fabrics. These results indicate that CPHDT increased the flame retardancy of cotton fabrics by inhibiting the formation of levoglucosan in cotton fibers during combustion.